2019
DOI: 10.1007/s11032-019-0994-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic distance and the relationship with heterosis and reproductive behavior in tetraploid bahiagrass hybrids

Abstract: Bahiagrass (Paspalum notatum Flüggé) is one of the main components of the South American grasslands, and it is cultivated for forage and turf around the world. At present, hybridization is the most common breeding technique for the species, and its goal is to obtain superior apomictic hybrids. The objective of the present study was to determine the relationship between heterosis, reproductive behavior, and genetic distances between parents in tetraploid bahiagrass. Genetic distance between 24 sexual tetraploid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 52 publications
4
36
1
2
Order By: Relevance
“…In the present study, we observed a positive signi cant correlation between grandparent heterobeltiosis for bunch weight and genetic distance between NARITA parents. These results agree with those of Marcón et al [40] who also reported a positive relationship between genetic distances among parents and heterosis for forage yield in bahiagrass (Paspalum notatum). However, these results contradict with what was observed by Tenkouano et al [31] in triploid plantains and secondary triploid plantain-derived hybrids.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we observed a positive signi cant correlation between grandparent heterobeltiosis for bunch weight and genetic distance between NARITA parents. These results agree with those of Marcón et al [40] who also reported a positive relationship between genetic distances among parents and heterosis for forage yield in bahiagrass (Paspalum notatum). However, these results contradict with what was observed by Tenkouano et al [31] in triploid plantains and secondary triploid plantain-derived hybrids.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding the occurrence of heterosis in P. notatum , we have already demonstrated that crossing very distant parents favors increasing the level of heterosis for forage yield (Marcón et al., 2019). In this work, given that the SSTP and apomictic genotypes used as male parents have different origins, a high genetic distance could be expected between them.…”
Section: Discussionmentioning
confidence: 91%
“…The occurrence of heterosis in the progenies obtained by the two breeding techniques was evaluated following the methodology proposed by Marcón et al. (2019). This methodology allowed determination of the genetic effects associated with the expression of forage yield and the proportion of families exhibiting heterosis.…”
Section: Methodsmentioning
confidence: 99%
“…These species undergo asexual propagation by seeds (Nogler, 1984), which allows the fixation of hybrid vigor in apomictic individuals and their use in the creation of uniform pastures (Jank et al, 2011). Experimental field data showed that aposporous apomixis in tropical forage grasses follows 1:1 Mendelian segregation, indicating monogenic inheritance (Savidan, 1981;Valle et al, 1994;Chen et al, 2000;Savidan, 2000), although a recent study suggests that this reproductive mode should be treated as a quantitative trait (Marcón et al, 2019), and provide evidence of the uncoupling of apomixis in neo-apomictic species, such as guinea grass (Kaushal et al, 2008;Kaushal et al, 2019). Molecularly, the apospory-specific genomic region (ASGR), which is responsible for apospory, is highly conserved among apomictic species (Gualtieri et al, 2006).…”
Section: Introductionmentioning
confidence: 99%